2005
DOI: 10.1530/rep.1.00742
|View full text |Cite
|
Sign up to set email alerts
|

The tapeworm Ligula intestinalis (Cestoda: Pseudophyllidea) inhibits LH expression and puberty in its teleost host, Rutilus rutilus

Abstract: The tapeworm Ligula intestinalis occurs in the body cavity of its cyprinid second intermediate host, in this study the roach Rutilus rutilus, and inhibits host gonadal development. The mechanism by which infected fish are prevented from reproducing is unknown. Comparison of parameters, such as body length and weight, and condition factor and age, between infected and uninfected individuals, indicated only minor effects of parasitism on growth and condition. In contrast, seasonal gonadal development, as observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 26 publications
7
47
0
Order By: Relevance
“…Also, many researchers have studied some effects of this parasite for fish host such as growth, endocrine system, gonadal development and had determined that L. intestinalis was caused many pathogenic effect on host fish. The parasite can cause damage to the host fish specimens especially by compression and atrophy of vital organs including the gonads, liver in the coelomic cavity of the infected fish (Öztürk and Altınel, 2001;Jopling and Taylor, 2003;Oğuz et al, 2004;Carter et al, 2005;Hecker and Karbe, 2005;Dejen et al, 2006). Similarly, in present study, macroscopic investigations showed that stomachs of fish specimens were swollen and gonads were deformed.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Also, many researchers have studied some effects of this parasite for fish host such as growth, endocrine system, gonadal development and had determined that L. intestinalis was caused many pathogenic effect on host fish. The parasite can cause damage to the host fish specimens especially by compression and atrophy of vital organs including the gonads, liver in the coelomic cavity of the infected fish (Öztürk and Altınel, 2001;Jopling and Taylor, 2003;Oğuz et al, 2004;Carter et al, 2005;Hecker and Karbe, 2005;Dejen et al, 2006). Similarly, in present study, macroscopic investigations showed that stomachs of fish specimens were swollen and gonads were deformed.…”
Section: Resultssupporting
confidence: 68%
“…According to Williams and Hoole (1992), numerous ecological and pathological studies have revealed that the parasite can seriously affect the population dynamics of both wild fish and those involved in aquaculture. There is limited data on relation of the parasite and its fish host R. rutilus (Kennedy and Burrough, 1981;Loot et al, 2001;Oğuz et al, 2004;Carter et al, 2005). The aim of the present study is to determine the occurrence of the parasites on host and investigate the effects of parasite for condition and length-weight relationship of host fishes living in Büyükçekmece Reservoir.…”
Section: Introductionmentioning
confidence: 97%
“…Tapeworm infections in the three-spined stickleback (Gasterosteus aceleatus) did impact fish reproduction and was manifested as a decrease in ovum mass (Heins and Baker 2003). Carter et al (2005) reported decreases in condition, gonadal development, and a reduction of almost 50% in gonadotropin concentration in roach, Rutilus rutilus. Laboratory experimentation is needed to fully assess the impact of B. acheilognathi on cyprinid reproduction in order to account for the above mentioned confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed variations of testicular weight instead of the sexual behaviors of sparganuminfected mice. Recently, the loach (Rutilus rutilus) infected with a pseudophyllidean tapeworm, Ligula intestinalis, showed approximately 50% less gonadotropin (LH) contents than non-infected fish and its negative effects on gonadal development in infected fish (Carter et al, 2005). Therefore, the present results suggest that the sparganum, i.e., a larval stage of pseudophyllidean tapeworm, may interact with the brain-pituitary-gonadal axis and affect gonadal development of the mouse host.…”
mentioning
confidence: 68%